Crosstalk between autophagy and ferroptosis mediate injury in ischemic stroke by generating reactive oxygen species - Xing-Yu Zhang; Ping-Ping Han; Yi-Ning Zhao; Xin-Ya Shen; Xia Bi (Heliyon, 2024)
Stroke represents a significant threat to global human health, characterized by high rates of morbidity, disability, and mortality. Predominantly, strokes are ischemic in nature. Ischemic stroke (IS) is influenced by various cell death pathways, notably autophagy and ferroptosis. Recent studies have increasingly highlighted the interplay between autophagy and ferroptosis, a process likely driven by the accumulation of reactive oxygen species (ROS). Post-IS, either the inhibition of autophagy or its excessive activation can escalate ROS levels. Concurrently, the interaction between ROS and lipids during ferroptosis further augments ROS accumulation. Elevated ROS levels can provoke endoplasmic reticulum stress-induced autophagy and, in conjunction with free iron (Fe2+), can trigger ferroptosis. Moreover, ROS contribute to protein and lipid oxidation, endothelial dysfunction, and an inflammatory response, all of which mediate secondary brain injury following IS. This review succinctly explores the mechanisms of ROS-mediated crosstalk between autophagy and ferroptosis and the detrimental impact of increased ROS on IS. It also offers novel perspectives for IS treatment strategies.